Peningkatan Mutu Proses Pembuatan Cat Solvent dengan Metode Taguchi di PT JI - Azwir, Hery Hamdi; Mahfud (Jurnal Optimasi Sistem Industri, 2018)
In a manufacturing process, quality is not only seen from the final product, but also manufacturing process. PT JI located in Cikarang is a company that produces paints and powder coating. Currently, the company has problems with 24.16% products that need rework or additional process. To increase productivity, PT JI applies the A3 project that is Right First Time (RFT). RFT is how to create a product with a one-time process and produce a product that has good quality on the first test. The average percentage of total RFT products in September 2016-January 2017 was 75.84%. This result is still below the company target of 80%. This study found the source of problems analyzed the manufacturing process using control chart, process capability, fishbone, and pareto. Taguchi method and ANOVA are applied to improve the design process. The application of the Taguchi Method shows that the factors which influence the value of viscosity quality are number of White Spirit, Number of Genekyd, Total Tio2 (kaolin), and mixing temperature, where each factor has an optimal level of 26.01%, 56.07%, 18.78% and 45oC. Then, it is found that all control factors have significant effect on viscosity value from ANOVA analysis. The application of this Taguchi method increases the process capability to Cp = 1.68 and Cpk = 1.43 from Cp = 0.29 and Cpk = 0.18, as well as an increase in RFT percentage of 5.78% or to 81.62% over the last two months.